Potential of Water Extract of The White Frangipani (Plumeria acuminate) and Hibiscus (Hibiscus tiliaceus) Leaves Powder as Textile Natural Dyes - Sri Mulyani; Kris Siska Aristia; Ardia Putri Sabrina; Afifatul Arfiah; Badrun Niam (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Synthetic dyes have a high environmental impact, especially on waters. The use of natural dyes for textiles provides new hope for ecological improvement. This article is to find out the yield of water extract of white frangipani (Plumeria acuminate) and hibiscus (Hibiscus tiliaceus) leaves-powder, as well as to find out whether the water extracts have potential as textile natural dyes. Natural dyes must have a good quality of fastness. For this reason, the color fastness tests for washing with a launder meter and colorfastness against rubbing with a crock meter are performed. Colorfastness is assessed by comparing color changes to washing with grayscale and color changes due to staining on fabric with staining scale. The rubbing test is carried out on the wet and dry cloth. Cotton and polyester fabrics are samples that will be colored. Fixers used to bind dyes are Al2(SO4)3, CaCO3, and FeSO4.H2O. The results show that the water extraction of hibiscus and white frangipani leaves powder gave a yield of 11% (w/w) and 27 % (w/w), respectively. The test of colorfastness against washing showed that both water extract of the white frangipani dan hibiscus leaves has a pretty good average quality in staining scale but less in grayscale. The test against rubbing shows that the type of fixer used affects the quality of the colorfastness, but in general, the water extract of white frangipani leaves gives better quality as a potential of natural dye than hibiscus leaves